NMDA and group I metabotropic glutamate receptors activation modulates substance P release from the arcuate nucleus and median eminence - Caruso, Carla Mariana (2006)
Glutamate participates in the regulation of secretion of several neuropeptides, including substance P (SP). Glutamate acts through ionotropic (iGluRS) and metabotropic (mGluRS) receptors. We have investigated whether glutamate receptor agonists and antagonists could affect SP release from the arcuate nucleus and the median eminence (ARC/ME). An increase in SP-like immunoreactivity (SP-LI) release from ARC/ME was induced by glutamate and N-methyl-D-aspartate (NMDA). This increase was prevented by D-(-)-2-amino-5-phosphono pentanoic acid  (DAP5) (0.1 mM), a specific NMDA antagonist and by (RS)-1-aminoindan-1,5-dicarboxylic acid  (AIDA) (0.1 mM), a selective antagonist of group I mGluR. The selective non-NMDA receptor antagonist 6,7-dinitroquinoxaline-2,3(1H-4H)-dione (DNQX) (0.1 mM) and (RS)-a-methyl-4-tetrazolylphenylglycine (MTPG) (0.1 mM), a group II and III mGluRs antagonist, did not affect the stimulatory effect of glutamate. A group I selective agonist, (S)-3,5-dihydroxyphenylglycine (DHPG) induced a significant increase in SP-LI release. Supporting the participation of nitric oxide (NO) in the effect of glutamate on SP-LI release, NAME (0.5 mM), a NO synthase inhibitor, reduced the glutamate–induced increase in SP-LI release from ARC/ME. Similarly, glutamate did not induce an increase in SP-LI release in the presence of meloxicam (0.1 mM) (a cyclooxygenase-2 specific inhibitor) indicating that prostaglandins production may also be involved in the glutamate effect. These data indicate that glutamate increases SP-LI release from the ARC/ME by acting through NMDA and group I mGluRs in the male rat. This stimulatory effect could be mediated by nitric oxide and prostaglandin production.